Pyocyanin biosynthesis protects Pseudomonas aeruginosa from nonthermal plasma inactivation. Issue 6 (15th March 2022) - Zhou, Huyue; Yang, Yi; Shang, Weilong; Rao, Yifan; Chen, Juan; Peng, Huagang; Huang, Jingbin; Hu, Zhen; Zhang, Rong; Rao, Xiancai
Summary: Pseudomonas aeruginosa is an important opportunistic human pathogen, which raises a worldwide concern for its increasing resistance. Nonthermal plasma, which is also called cold atmospheric plasma (CAP), is an alternative therapeutic approach for clinical infectious diseases. However, the bacterial factors that affect CAP treatment remain unclear. The sterilization effect of a portable CAP device on different P. aeruginosa strains was investigated in this study. Results revealed that CAP can directly or indirectly kill P. aeruginosa in a time‐dependent manner. Scanning electron microscopy and transmission electron microscope showed negligible surface changes between CAP‐treated and untreated P. aeruginosa cells. However, cell leakage occurred during the CAP process with increased bacterial lactate dehydrogenase release. More importantly, pigmentation of the P. aeruginosa culture was remarkably reduced after CAP treatment. Further mechanical exploration was performed by utilizing mutants with loss of functional genes involved in pyocyanin biosynthesis, including P. aeruginosa PAO1 strain‐derived phzA1 ::Tn, phzA2 ::Tn, Δ phzA1 /Δ phzA2, phzM ::Tn and phzS ::Tn, as well as corresponding gene deletion mutants based on clinical PA1 isolate. The results indicated that pyocyanin and its intermediate 5‐methyl phenazine‐1‐carboxylic acid (5‐Me‐PCA) play important roles in P. aeruginosa resistance to CAP treatment. The unique enzymes, such as PhzM in the pyocyanin biosynthetic pathway, could be novel targets for the therapeutic strategy design to control the growing P. aeruginosa infections. Abstract : Cold atmospheric plasma (CAP) produced by a portable CAP device can directly or indirectly kill P. aeruginosa in a time‐dependent manner. Importantly, pigmentation of the P. aeruginosa culture was remarkably reduced after CAP treatment. Further mechanical exploration based on pigment mutants indicated that pyocyanin and its intermediate 5‐methyl phenazine‐1‐carboxylic acid (5‐Me‐PCA) play important roles in P. aeruginosa resistance to CAP treatment.